Pengaruh Edukasi Menggunakan Media Flipchart Terhadap Pengetahuan dan Tindakan Kepatuhan Konsumsi Tablet Tambah Darah untuk Mencegah Anemia pada Ibu Hamil di Puskemas Wara Utara Kota - Syahruni Mursaha; Resty Ryadinency (Indonesian Journal of Science and Public Health, 2025)
Adherence to the consumption of blood supplement tablets is important because it is a factor that causes the incidence of anemia in pregnant women. Anemia during pregnancy can have a negative impact on both mother and baby. An intervention is needed to prevent this from happening by providing education, one of which uses flipchart media. Objective: to determine the effect of education using flipchart media on knowledge and compliance with the consumption of blood supplement tablets to prevent anemia in pregnant women at the Puskesmas Wara Utara Kota in 2024. Methods: This study is a quantitative study with a pre experimental approach with a one group pretest posttest design. The population in this study were pregnant women in the working area of Puskesmas Wara Utara Kota in 2024 as many as 78 respondents. Sampling in this study used the lemeshow formula, so that the number of samples produced was 26 respondents. The tool used to collect respondent data was a questionnaire. After that, the data were processed and analyzed by entering the data into SPSS, namely the analysis process based on univariate analysis (determination of frequency distribution), as well as bivariate analysis using nonparametric test (wilcoxon test), with a level of significance (0.05). Results: there is an effect of education with the use of flipchart media on respondents' knowledge with a value of (p = 0.004) and compliance with the consumption of blood supplement tablets with a value of (p = 0.000). Conclusion: there is an effect of education using flipchart media on knowledge and compliance with the consumption of blood supplement tablets to prevent anemia in pregnant women at the Puskesmas Wara Utara Kota in 2024.